Analysis of Generations of Wind Power Technologies Based on Technology Life Cycle Approach - Madavar, M. Dehghani; Nezhad, MH Ghodousi; Aslani, Dr. Alireza; Naaraonja, Dr. Marja (Distributed Generation & Alternative Energy Journal, 2017)
Utilization of renewable energy technologies is one of the strate- gies of the governments in order to increase the level of energy security. One of the main renewable energy resources with fast utilization growth is wind power. However, development of wind power is highly de- pended on its related technologºies. Therefore, wind power technology forecasting is an indispensable requirement to understand how each of the wind energy domains will improve in the future. This research is to focus on the analysis of wind power technologies based on the technol- ogy life cycle approach. The contributions can help researchers, technol- ogy futurists, and policy makers to focus better on the related R&D and utilization policies.